Is the performance of firms following seasoned equity issues anomalous? - Bayless, Mark; Jay, Nancy R. (Journal of Banking & Finance, 2003)
The hypothesis that negative abnormal returns following an equity issue are anomalous assumes the use of the correct benchmark. The alternative hypothesis assumes that an incorrect benchmark has been used or that benchmarks change following an issue. We evaluate these assumptions by examining the performance of SEO firms during periods when there was no issue activity. Results indicate that SEO firms experience positive abnormal returns away from the issue window and that positive performance is most pronounced for small SEO firms. These and other results are inconsistent with the alternative hypothesis.